(untitled) (Journal of Health, Population and Nutrition, 2009)
Since the beginning of the Safe Motherhood Initiative, India has accounted for at least a quarter of maternal deaths reported globally. India’s goal is to lower maternal mortality to less than 100 per 100,000 livebirths but that is still far away despite its programmatic efforts and rapid economic progress over the past two decades. Geographical vastness and sociocultural diversity mean that maternal mortality varies across the states, and uniform implementation of health-sector reforms is not possible. The case study analyzes the trends in maternal mortality nationally, the maternal healthcare-delivery system at different levels, and the implementation of national maternal health programmes, including recent innovative strategies. It identifies the causes for limited success in improving maternal health and suggests measures to rectify them. It recommends better reporting of maternal deaths and implementation of evidence-based, focused strategies along with effective monitoring for rapid progress. It also stresses the need for regulation of the private sector and encourages further public-private partnerships and policies, along with a strong political will and improved management capacity for improving maternal health. Key words: Delivery; Health indicators; Healthcare; Maternal health; Maternal health services; Maternal mortality; India doi: 10.3329/jhpn.v27i2.3363 J Health Popul Nutr 2009 April;27(2):184-201